A Pathway for Northern Hemisphere Extratropical Cooling to Elicit a Tropical Response - Matthew T. Luongo; Shang‐Ping Xie; Ian Eisenman; Yen‐Ting Hwang; Hung‐Yi Tseng (Geophysical Research Letters, 2023)
Abstract Previous studies have found that Northern Hemisphere aerosol‐like cooling induces a La Niña‐like response in the tropical Indo‐Pacific. Here, we explore how a coupled ocean‐atmosphere feedback pathway communicates and sustains this response. We override ocean surface wind stress in a comprehensive climate model to decompose the total ocean‐atmosphere response to forced extratropical cooling into the response of surface buoyancy forcing alone and surface momentum forcing alone. In the subtropics, the buoyancy‐forced response dominates: the positive low cloud feedback amplifies sea surface temperature (SST) anomalies which wind‐driven evaporative cooling communicates to the tropics. In the equatorial Indo‐Pacific, buoyancy‐forced ocean dynamics cool the surface while the Bjerknes feedback creates zonally asymmetric SST patterns. Although subtropical cloud feedbacks are model‐dependent, our results suggest this feedback pathway is robust across a suite of models such that models with a stronger subtropical low cloud response exhibit a stronger La Niña response.